Nitrogen fertilization affects yields and storage compound contents in seeds of field-grown soybeans cv Enrei (Glycine max. L) and its super-nodulating mutant En-b0-1 through changing N2 fixation activity of the plants. Issue 2 (3rd March 2020) - Hamaguchi, Hideo; Yamamoto, Naoki; Takeda, Akinori; Masumura, Takehiro; Sugimoto, Toshio; Azuma, Tetsushi
ABSTRACT: We compared the protein and oil contents, seed yields, and natural abundance of 15 N (σ 15 N) of seeds from the plants of the cultivar Enrei, which has moderate nodulating ability (Enrei) with those of its two near-isogenic lines (NILs), a super-nodulating genotype of Enrei, i.e., En-b0-1, and a non-nodulating genotype of Enrei, i.e., En1282. Plants of these three genotypes were grown on four types of field plots with different types of urea coated slow-release nitrogen (N) fertilizers (CUSLNFs) which delivered N in different manners during plant growth . The seed yield of the En1282 plants was similar to that of the Enrei plants but much greater than that of the En-b0-1 plants when the plants were grown on the field to which a CUSLNF with a long lifespan was applied. The amounts of protein per seed were positively correlated with those of oil per seed in the case of En1282 plants irrespective of the field N conditions. The seed protein contents were proportional to the seed weight in both En1282 and Enrei plants. Such a relationship was not observed in the En-b0-1 plants, and the protein and oil contents in the seeds of En-b0-1 plants were negatively correlated with each other. These observations suggested that the N supply to maturing seeds was a key to the protein contents in the En1282 and Enrei plants and that the C supply to maturing seeds was a key to the protein contents in the En-b0-1 plants. The comparison of the σ 15 N values, protein contents, and seed yields of seeds from En1282 plants suggested that the Enrei plants assimilated considerable amounts of N from the soil during the late plant growth. We concluded that high N2 fixation activity depressed the amounts of oil per seed and changed the protein and oil contents in soybean seeds.